Pleadings, Minutes of Public Sittings and Documents (Pleadings, Minutes of Public Sittings and Documents / Mémoires, Procès-Verbaux des Audiences Publiques et Documents Ser., 2017)
This volume contains the texts of written pleadings, minutes of public sittings and other documents from the proceedings in The "Enrica Lexie" Incident (Italy volume India), Provisional Measures . The documents are reproduced in their original language. The Tribunal delivered its Order on 24 August 2015. It is published in the ITLOS Reports 2015 . Le présent volume reproduit les pièces de la procédure écrite, les procès-verbaux des audiences publiques et d'autres documents relatifs à la procédure concernant L'incident de l'« Enrica Lexie » (Italie c. Inde), mesures conservatoires . Les documents sont publiés dans la langue originale utilisée. Le Tribunal a rendu son ordonnance le 24 août 2015. L'ordonnance est publiée dans le TIDM Recueil 2015 .